Preparation and Antifungal Activities of Chitosan from Apple-Snail (Pila Ampullacea) Shells as Preserving Agent for Postharvest Podang Mango (Mangifera Indica L.) Cv Podang - Riska Surya Ningrum; Aisyah Ramadani; Reny Rosalina; Desy Yustiyani; Rio Altha Reyzando (Indonesian Journal of Applied Research (IJAR), 2021)
Podang mango, an endemic mango from Kediri, has a short post-harvest shelf life that accelerates by physiological factors and pathogenic fungal contamination. Chitosan reported as an active compound for coating. The apple-snail was reported to contain chitosan in its shell. The purposes of this study are to synthesis chitosan from Pila ampullacea, examine anti-fungal activities to Fusarium oxysporum and Aspergillus ochraceus, and verify the effect of chitosan coating on shelf life and quality of Podang mango. The effect of chitosan coating on fruit quality was analyzed using three treatments which were negative control, chitosan, and chitosan-gelatin with 3 replications. The parameters measured were color, texture, aroma, water content, vitamin C, and weight loss. Results showed that chitosan synthesized from P. ampullacea had 53.56 degrees of deacetylation. Antifungal activity test of chitosan 2% had the highest inhibitory activity against F.oxysporum and A.ochraceus growth with 14.46 mm and 10.33 mm inhibition zone. Coating with chitosan statistically affected fruit quality for 14 days of storage (sig <0.05). Chitosan-gelatin coating is the best treatment in reducing weight loss (8.97%), maintain aroma (sweet fragrance), texture (soft), water content (84%), and vitamin C (0.182%), while the color (reddish yellow) was more influenced by Chitosan coating. Chitosan coated with gelatin is recommended for application on Podang mangoes.